Preparing competent citizens through appropriate instructional approach: How do instructors in three Ethiopian universities conceptualize and practice 21st century pedagogical skills? - Amsalu Molla Getahun; Mulugeta Yayeh Worku; Alemayehu Bishaw Tamiru (College of education, Bahir Dar University, 2023)
This study aimed to investigate how instructors at three Ethiopian universities conceptualize and practice 21st century skills in classrooms. To achieve this purpose, a qualitative case study design was employed. Using a purposive sampling method, three universities in the Amhara national regional state of Ethiopia were selected. From these universities, ten participants were selected purposively. Semi-structured interviews and observation were used to collect data essential for the study. The data collected through these methods were thematically analyzed. The results revealed that participants had a limited understanding of 21st century skills. To be specific, their conceptions reflected the conventional pedagogical approach rather than the pedagogy of the 21st century. On the other hand, participants believe that 21st century skills are important for both instructors and their students. However, they had difficulties to practice these skills in the teaching-learning process. Finally, the implications of these findings for future research and policy initiatives are presented.